2016
DOI: 10.1104/pp.15.01859
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Profiling of Ethylene Response Factor Expression Identifies Ripening-Associated ERF Genes and Their Link to Key Regulators of Fruit Ripening in Tomato

Abstract: (E.M.); 0000-0001-7707-7776 (J.-P.R.); 0000-0002-5725-885X (J.P.).Our knowledge of the factors mediating ethylene-dependent ripening of climacteric fruit remains limited. The transcription of ethylene-regulated genes is mediated by ethylene response factors (ERFs), but mutants providing information on the specific role of the ERFs in fruit ripening are still lacking, likely due to functional redundancy among this large multigene family of transcription factors. We present here a comprehensive expression profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
169
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(176 citation statements)
references
References 62 publications
(99 reference statements)
2
169
1
4
Order By: Relevance
“…Recent genome-wide bioinformatics analyses identified a total of 146 members in the tomato AP2/ERF superfamily, of which 77 members belong to the ERF family (Sharma et al, 2010; Pirrello et al, 2012; Liu et al, 2016). Expression profiling analyses revealed that a large set of the tomato ERF genes are differentially induced by developmental cues, hormones and various stress factors (Gu et al, 2000; Tournier et al, 2003; Sharma et al, 2010; Pirrello et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent genome-wide bioinformatics analyses identified a total of 146 members in the tomato AP2/ERF superfamily, of which 77 members belong to the ERF family (Sharma et al, 2010; Pirrello et al, 2012; Liu et al, 2016). Expression profiling analyses revealed that a large set of the tomato ERF genes are differentially induced by developmental cues, hormones and various stress factors (Gu et al, 2000; Tournier et al, 2003; Sharma et al, 2010; Pirrello et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Expression profiling analyses revealed that a large set of the tomato ERF genes are differentially induced by developmental cues, hormones and various stress factors (Gu et al, 2000; Tournier et al, 2003; Sharma et al, 2010; Pirrello et al, 2012). Functional studies have characterized a number of tomato ERF genes, e.g., SlERF1, Sl-ERF2, TSRF1, SlAP2a, Sl-ERF.B3, SlERF6, SlERF36 , and SlERF52 , that play important roles in regulating growth and developmental processes including seed germination, seedling development, stomatal density, fruit ripening, and flower pedicel abscission (Pirrello et al, 2006; Li et al, 2007; Zhang et al, 2008, 2009; Chung et al, 2010; Lee et al, 2012; Liu et al, 2013, 2016; Upadhyay et al, 2013; Liu M. et al, 2014; Nakano et al, 2014). Whereas TERF1, TERF2, TSRF1, JERF1, JERF3, LeERF3b, Sl-ERF.B.3 , and ERF5 were found to be involved in regulating abiotic stress response (Huang et al, 2004; Wang et al, 2004; Zhang et al, 2004a,b, 2007, 2010; Chen et al, 2008; Wu et al, 2008; Quan et al, 2010; Zhang and Huang, 2010; Tian et al, 2011; Pan et al, 2012; Klay et al, 2014), Pti4, Pti5, Pti6, TSRF1 , and SlERF3 have been demonstrated to play key roles in regulating defense responses against pathogens and insect pests (Zhou et al, 1997; He et al, 2001; Gu et al, 2002; Wu et al, 2002, 2015; Zhang et al, 2004b, 2007; Pan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there are 85 members of ERFs in tomato using raw EST data in various public repositories, among which 57 ERFs were found to be differentially expressed during temporal stages of tomato fruit development (Sharma et al, 2010). More recently, the TomExpress on-line tool revealed that 55 out of 77 ERF family genes display a ripening-associated expression pattern, with 27 being up-regulated during ripening and the remaining 28 being down-regulated, indicating that different ERFs may have diverse roles in fruit ripening (Liu et al, 2016). A recent study demonstrated that MaERF11 was down-regulated in peel and pulp of banana fruit during ripening and after being treated with ethylene (Xiao et al, 2013), suggesting that MaERF11 may play a role in fruit ripening.…”
Section: Maerf11 Acts As a Crucial Transcriptional Repressor In Fruitmentioning
confidence: 99%
“…To our knowledge, most of these have not been associated previously with the fruit epidermis/cuticle; however, several are known to regulate early fruit development, including the MADS box gene TAGL11 (Mejía et al, 2011), or fruit ripening, such as the MADS box gene RIPENING INHIBITOR (RIN [Solyc05g012020]; Vrebalov et al, 2002;Kosma et al, 2010), as well as several ethylene-responsive TFs (Liu et al, 2016). The differentially expressed TFs included those with a possible link to the circadian clock, with two genes (Solyc01g095030 and Solyc10g084370) encoding MYB-related TFs of the REVEILLE family (Farinas and Mas, 2011), one of which was expressed at lower levels in gpat6-a, and six genes encoding CONSTANS-like TFs (Valverde, 2011), one of which (Solyc12g005660) was expressed at much lower levels.…”
Section: The Gpat6-a Mutant Has Abnormal Fruit Cuticle Thickness Andmentioning
confidence: 99%